Management and clinical consequences of red blood cell antibodies in pregnancy: A population‐based cohort study. (2nd September 2021) - Liu, Shengxin; Ajne, Gunilla; Wikman, Agneta; Lindqvist, Caroline; Reilly, Marie; Tiblad, Eleonor
Abstract: Introduction: Anti‐D alloimmunization is the most common cause of severe hemolytic disease of the fetus and newborn (HDFN). The management of pregnancies affected by less frequent red blood cell (RBC) antibodies poses a challenge to clinicians, and perinatal outcomes are less well described. This study aimed to describe the frequency of clinically significant RBC antibodies in our pregnant population and analyze the risk of prenatal and postnatal treatment for HDFN in relation to our national risk classification system and management guidelines. Material and methods: A retrospective cohort study in the population of all alloimmunized singleton pregnancies in the Stockholm region 1990–2016. Descriptive summaries of different RBC antibodies and pregnancy outcomes were presented, the risks of intrauterine blood transfusion (IUT) and neonatal treatment for HDFN were estimated by type of antibodies. Results: Of the 1724 alloimmunized pregnancies, 1079 (63%) were at risk of HDFN and constituted our study cohort. Anti‐D was detected in 492 (46%) pregnancies, followed by anti‐E in 161 (15%), and anti‐c in 128 (12%). Eighty‐seven (8%) pregnancies had IUT, with the highest risk in pregnancies affected by anti‐D combined with other antibodies. The maximum titer recorded before IUT was 64 or above, except for two pregnancies affected by anti‐c, for which the maximum titers were 8 and 16. For the 942 (95%) live‐born neonates from 992 alloimmunized pregnancies without IUT, the median gestational age at birth was 38 +5 weeks compared with 35 +5 weeks for those who had IUT. Neonatal treatment was most common in the anti‐D alone and anti‐D combined groups, with 136 (57%) and 21 (44%), respectively, treated with phototherapy and 35 (15%) and 9 (20%) receiving exchange transfusions, respectively. For pregnancies complicated by moderate‐ and low‐risk antibodies, phototherapy was less frequent (32 [36%] and 21 [19%]) and exchange transfusion was rare (5 [6%] and 3 [3%]). Conclusions: Anti‐D, especially in combination with other antibodies, presents the highest risk of severe HDFN. The classification of less frequent and less well‐known RBC antibodies into risk groups can help clinicians in assessing the risk of HDFN and counseling alloimmunized pregnant women regarding the risk of prenatal and postnatal treatments.